The Innovation of Islamic Finance in The Era of Digital Transformation: A Multidisciplinary Analysis of Opportunities and Challenges in Southeast Asia - Euis Amalia (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
The global Islamic finance industry has experienced significant growth with assets reaching 3.8 trillion, yet faces major challenges in integrating digital technology while maintaining Shariah compliance. This study aims to analyze the opportunities and challenges of Islamic finance innovation in the era of digital transformation with a focus on the Southeast Asian region. This research employs a qualitative descriptive-analytical approach using literature review methodology, collecting data from the State of Global Islamic Economy Report, annual reports of Islamic financial institutions, and related academic publications. The analysis synchronizes digital technology developments with the principles of Maqasid al-Shariah. The results show that blockchain and fintech technologies can improve operational cost efficiency by 20-30% while strengthening transparency and Shariah compliance. However, significant challenges include regulatory gaps, debates on the legal status of cryptocurrency, and low digital financial literacy among rural Muslim communities (49% in Indonesia). This study concludes that the successful digital transformation of Islamic finance requires collaboration between scholars, technologists, and regulators to develop a comprehensive framework.